2014
DOI: 10.1111/ssm.12071
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Project‐Based Learning on Students' Academic Achievement, Attitude, and Retention of Knowledge: The Subject of “Electricity in Our Lives”

Abstract: The aim of this study is to analyze the effects of project‐based learning on students' academic achievement, attitude, and retention of knowledge in relation to the subject of “Electricity in Our Lives” in a fourth‐grade science course. The study was conducted in a quasi‐experimental design as a “pre‐test, post‐test with control group.” In the experimental group, the unit was taught through the project‐based learning method. The measuring tools were administered to both groups before and after the applications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 27 publications
3
48
0
2
Order By: Relevance
“…It can be said that the STEM-PBL approach has a positive effect on the academic achievement of the vocational high school students in the direction of the question of "Does projectbased STEM education have an impact on the academic achievement of vocational high school students?" This result is consistent with the studies of Karaçalli and Korur (2014) Yıldırım and Altun (2015), are in parallel with the results of the present study. Conducting the STEM-PBL education for vocational high school students, which indicates in line results with the study of Chang et al (2015), is the original and most important part of this study.…”
Section: Discussion Conclusion and Implicationssupporting
confidence: 83%
“…It can be said that the STEM-PBL approach has a positive effect on the academic achievement of the vocational high school students in the direction of the question of "Does projectbased STEM education have an impact on the academic achievement of vocational high school students?" This result is consistent with the studies of Karaçalli and Korur (2014) Yıldırım and Altun (2015), are in parallel with the results of the present study. Conducting the STEM-PBL education for vocational high school students, which indicates in line results with the study of Chang et al (2015), is the original and most important part of this study.…”
Section: Discussion Conclusion and Implicationssupporting
confidence: 83%
“…Constructivist-inspired PBL, also known as project-based science learning, defines PBL as learning through projects that focus on problems in their real-life settings (Karaçalli & Korur, 2014). Grounded in the work of Krajcik, Czerniak, and Berger (1999), the principal features of project-based learning according to this definition of PBL include "constructing knowledge through trial and error, " "learning by doing, " and "applying new knowledge to new circumstances" (Colley, 2008;Singer, Marx, Krajcik, & Clay-Chambers, 2000;von Glasersfeld, 1995).…”
Section: Constructivism or Project-based Learning Definitionsmentioning
confidence: 99%
“…Grounded in the work of Krajcik, Czerniak, and Berger (1999), the principal features of project-based learning according to this definition of PBL include "constructing knowledge through trial and error, " "learning by doing, " and "applying new knowledge to new circumstances" (Colley, 2008;Singer, Marx, Krajcik, & Clay-Chambers, 2000;von Glasersfeld, 1995). In contrast to ill-structured problem solving with minimal teacher guidance in the clinical medicine conception of PBL, project-based science learning typically features progress-report forms that teachers create to guide students' inquiry and knowledge construction processes (Karaçalli & Korur, 2014).…”
Section: Constructivism or Project-based Learning Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Karaçalli and Korur (2014) conducted a quasi-experimental study in Turkey with fourth-grade science students (equivalent to Year 5 in the UK) and found a statistically significant effect in terms of academic achievement and retention of knowledge for the project-based learning students. A US study that explored the effectiveness of a project-based approach in 2 nd grade (equivalent to Year 1 in the UK) social studies and content area literacy (Halvorsen, Duke, Brugar, Berka & Brown, 2012) reported positive outcomes for low-SES students and claimed that the project-based learning approach has the potential to help narrow the gap between low and high-SES students in social studies and literacy for 2 nd grade students.…”
Section: Pre-school and Primary Schoolmentioning
confidence: 99%